The Floating Acromion: A Rare and Previously Unreported Injury Possibly Requiring Surgical Stabilization - Simone J. M. Stoots; Robert J. Derksen (Case Reports in Orthopedics)
Acromion fractures are increasingly seen as a postoperative complication following reversed shoulder arthroplasty. However, traumatic fractures of the acromion, usually caused by direct trauma, are rare. Therefore, the current literature lacks standardized clinical guidelines regarding the surgical treatment of these kinds of fractures. We present a traumatic acromion fracture and concomitant distal clavicle fracture, resulting in a so-called “floating acromion.” A fifty-four-year-old female patient was presented at the Emergency Department following a fall from the stairs. She complained of severe pain in the left shoulder. Radiographic evaluation of the left shoulder revealed an acromion fracture and concomitant distal clavicle fracture. Initially, since there was no dislocation, this “floating acromion” was treated conservatively. However, after 4 weeks, no improvement in pain was seen and a control CT scan revealed no callus formation. Considering the possibility that this could be a biomechanically unstable injury, together with the persistent severe pain, it was decided to proceed with surgical treatment. A lateral clavicle plate was used to stabilize the acromion fracture. Postoperatively, the patient was provided with a sling. She was regularly seen at the outpatient clinic. After two weeks of circumduction exercises, she was allowed to build up active movement under the supervision of a shoulder physiotherapist. Nevertheless, she developed a frozen shoulder. However, our patient fully recovered with complete restoration of shoulder function. Therefore, for operative management of acromion fractures, we suggest the use of a lateral clavicle plate which fits remarkably well on the lateral spine and acromion.